UJI AKTIVITAS EKSTRAK KENTAL ETANOL PANDAN HUTAN JENIS BARU (Freycinetia sessiliflora RIZKI) TERHADAP PERTUMBUHAN BAKTERI Staphylococcus aureus - Fitri Sri Rizki; Ade Ferdinan (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2020)
A new species of the pandanus (Freycinetia sessiliflora Rizki) is one species found in the year 2015 on Passi Mount, West Kalimantan. The researchers found the pandanus new species which is very different from other pandanus. The results of skrinning phytochemical leaves of the pandanus (Freycinetia sessiliflora Rizki) containing a compound of a secondary metabolite namely alkaloid , flavonoid , terpenoid-steroid , saponin , phenol and tannin. Based on secondary metabolite compounds which done research to test the activity of the pandanus extract bacteria Staphylococcus aureus. Plant extracts pandanus in get maceration with a solvent use of ethanol to achieve an extract will be used to test the activity of obstruent against bacteria Staphylococcus aureus by using the Then it will be the measurement of clear zone formed about paper discs .Analyze by anova data in one direction with the levels of trust 95 %. Based on the research done an obstruent extracts the results of a new species of pandanus against bacteria staphylococcus aureus with an average diameter obstruent concentration 5% of 10,86, mm the concentration of 10 % of 11,46, mm the concentration of 15 % of 11,8, mm the concentration of 20% of 12,24 mm and the highest 25% of 12,9 mm.